PENGARUH PERTUMBUHAN EKONOMI, PENDAPATAN ASLI DAERAH (PAD) TERHADAP PENGALOKASIAN ANGGARAN BELANJA MODAL DI KOTA SERANG (Faletehan Jurnal Ekonomi dan Bisnis, 2024)
The aim of this research is to determine the effect of economic growth on the allocation of the capital expenditure budget in the city of Serang. Also know the influence of local original income (PAD) on the allocation of the capital expenditure budget in the city of Serang. This research uses secondary data. Data collection methods in this research are documents and literature study. The data analysis test tool uses multiple linear regression analysis, which is about the relationship between one dependent variable and more than one independent variable. Data is used using the SPSS application computer program which is then processed and conclusions are drawn for the validity of the classical assumption test data and multiple linear regression. Based on research results, economic growth does not have a significant effect on the allocation of the capital expenditure budget. Regional original income has a significant influence on the allocation of the capital expenditure budget. Economic growth, local original income (PAD) together simultaneously have a significant influence on the allocation of the capital expenditure budget. capital expenditure.